ATRIAL FIBRILLATION AND ARTERIAL HYPERTENSION: GENDER DIFFERENCES OF VENTRICULOATRIAL REMODELING WITH PRESERVED EJECTION FRACTION - Zh. D. Kobalava; E. V. Kokhan; G. K. Kiyakbaev; A. A. Shavarov (Рациональная фармакотерапия в кардиологии)
Today there is enough data on gender differences in regard to epidemiology, pathogenesis and prognostic value of atrial fibrillation (AF). Left atrial structural and functional changes associated with development and persistence of AF can be more significant for women than for men. Explanation for it can be provided by a higher prevalence of left ventricular diastolic dysfunction in women, which is strongly related with central aortic pressures. Many studies have shown gender differences of central pulse wave contour; however further investigations of their prognostic power and relationship with left atrial remodeling are needed. According to current guidelines for AF management rhythm control is not a superior treatment strategy compared with heart rate control. The subanalysis of RACE study showed that rhythm control in female patients with AF increased significantly the risk of composite endpoints including cardiovascular mortality, heart failure, thromboembolic events, bleedings, severe side effects of antiarrhythmic drugs and the need for a pacemaker implantation. It seems that in some cases rate control approach may be preferable in female patients with recurrent AF. The current management of AF is still suboptimal and one of the ways to increase effectiveness should take into consideration the gender differences of left atrial, left ventricular and arterial interaction. More relevant randomized studies will be required to confirm this hypothesis.